THE LEVEL OF LEARNING AUTONOMY OF ENGLISH STUDY PROGRAM STUDENTS IN UNIVERSITY OF JAMBI - Ravial Fandi (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
The present study identified the level of learning autonomy of English study program students at the University of Jambi. The quantitative method with the explanatory design was the method of the research. There was one instrument that was used to obtain the data, namely questionnaires. There were 403 in the academic year 2016, 2017, 2018, and 2019 but only 120 students participated in this research. Based on the discussion, there were 2 categorized of the level of learning autonomy students of the English study program at the University of Jambi. There are high levels and moderate levels of learning autonomy. The majority of all students in the English study program of the University of Jambi who answered the questionnaire were at a high level of learning autonomy. The percentage of the level of learning autonomy students of English education program at university of Jambi were seventy nine percent a high level of learning autonomy and twenty one percent a moderate level of learning autonomy. Meanwhile no one students identified a low level of learning autonomy.